The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00534-011-0472-8
|View full text |Cite
|
Sign up to set email alerts
|

Stented pancreaticojejunostomy (with video)

Abstract: Background/purpose Using a standardized technique for pancreaticojejunostomy that we term ''pair-watch suturing technique'', we prospectively analyzed the effects of a pancreatic stent tube for preventing pancreatic fistula and furthermore evaluated which perioperative factors had an influence on the development of pancreatic fistula. Operative procedure Before anastomosis, we imagine the faces of a pair of wristwatches on the jejunal hole and pancreatic duct. The first stitch was put between 9 o'clock on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Moreover, pancreatic anastomosis techniques are generally described in single-surgeon or singleinstitution studies often reporting low POPF rates of their preferred pancreatic anastomosis. 11,61,62 This is supported by the current data, showing a higher pooled incidence of POPF in multicenter and two-center trials compared to single-center trials. In the ISGPS position statement, it is stated that experienced surgeons at high-volume centers can decrease the incidence of POPF by performing a variety of techniques in diverse intraoperative situations.…”
Section: Hpbsupporting
confidence: 72%
“…Moreover, pancreatic anastomosis techniques are generally described in single-surgeon or singleinstitution studies often reporting low POPF rates of their preferred pancreatic anastomosis. 11,61,62 This is supported by the current data, showing a higher pooled incidence of POPF in multicenter and two-center trials compared to single-center trials. In the ISGPS position statement, it is stated that experienced surgeons at high-volume centers can decrease the incidence of POPF by performing a variety of techniques in diverse intraoperative situations.…”
Section: Hpbsupporting
confidence: 72%
“…8,30,31 However, these results are not consistent in the literature, and, in agreement with other studies, no predictors of POPF were identified in the present study. 13,32 It should be kept in mind that there are several key steps in creating a safe pancreaticoenteric anastomosis, which include the following: (1) the exact approximation of the enteral mucosa and the duct epithelium; (2) preservation of adequate blood flow at the pancreatic stump, requiring low-tension tying of the sutures; (3) identification and ligation of minor ductules on the cut surface of the pancreas; (4) elimination of dead space between the cut surface of the pancreas and the enteric serosa, where the autolytic pancreatic juice could accumulate and lead to anastomotic breakdown; (5) facilitation of pancreatic juice flow into the enteric lumen, especially during the first postoperative days when tissue edema is present, and, even more so, in the case of a soft pancreas with a normal amount of pancreatic secretions. Successful pancreatic surgery requires meticulous and standardized preoperative diagnostic workup (high-quality imaging and operative risk assessment) and the provision of highly specialized peri-and postoperative care and medication protocols.…”
Section: Discussionmentioning
confidence: 97%
“…For pancreaticojejunostomy, the first-layer anastomosis, which was a duct-to-mucosa anastomosis, was performed using PWST with 6-0 PDS II (Ethicon, Inc. Somerville, NJ, USA). This technique was conducted using 12 interrupted sutures oriented in a clock formation regardless of the MPD diameter [18][19][20]. This can be imagined as the faces of a pair of wristwatches, with the jejunal hole corresponding to the left-hand watch and the pancreatic duct hole to the right-hand one.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The procedures of pancreatoenteral anastomosis have not been standardized, and each institution performs their own preferred procedure, such as pancreaticogastrostomy, pancreaticojejunostomy, external tube drainage, the lost stent method and invagination; this diversity of procedures makes it difficult to evaluate the frequency of POPF [15][16][17]. Our institution reported the method of 12 interrupted-stitched duct-to-mucosa pancreaticojejunostomy, named the "pair-watch suturing technique (PWST)", which allowed us to standardize the method of pancreaticojejunostomy [18][19][20]. However, even though the anastomotic technique has progressed, POPF still has yet to be thoroughly prevented after PD, and the incidence of POPF in patients with soft pancreas has been reported to be particularly high; thus, the prevention of POPF in patients with soft pancreas is still under discussion [21][22][23].…”
Section: Introductionmentioning
confidence: 99%